Properties of Fine-Grained Cement Composites, with a Special Emphasis on Cement Screeds in Floor Constructions - Rada Radulović; Ljubo Marković; Vladimir Radojičić; Kristina Božić Tomić; Nikola Gvozdović (Applied Sciences, 2024)
Through experimental research and theoretical analysis, this study primarily aimed to compare the behavior of cement screeds made in a traditional manner with those made with the addition of microreinforcement. The study also explored the possibility of using electrofilter ash as a component of screeds, examining the advantages and disadvantages of partial substitution of cement with fly ash. The contribution of this article is the experimental research on the characteristics of fresh and hardened cement composites, as well as the parameters influencing the structure and behavior of cement screeds during their use. It has been determined that by using electrofilter ash as a partial replacement for cement, satisfactory values of physical–mechanical and deformation characteristics of fine-grained cement composite can be achieved. Through analysis of the obtained results and influential parameters of these composites, the optimal design approach has been explored. This relevant information could potentially provide reliable recommendations to designers and contractors for the production of quality and durable cement screeds.